ENDOCANNABINOIDS: A THERAPEUTIC OPTION TO CANCER TREATMENT - MAYORGA N., Fabio; CÁRDENAS S., Rosa H. (Vitae, 2009)
Scientific advances in Chemistry and Medicine now study wise ancestral popular usages of natural resources. Cannabis sativa>/I> has been traditionally used for medicinal and recreational purposes. However, its important psychoactive effects limit its use. Some governments allow its controlled use for medicinal purposes since the discovery of endogenous compounds with similar properties to cannabinoids (endocannabinoids) combined with the previous knowledge on CB1 and CB2 receptors on which they act. A great interest to discover new therapeutic substances for several pathologies treatment has grown increasingly the world over. The possibilities to take advantage of the endocannabinoids structures to design new molecules with antineoplastic activity are coming closer to this challenge, which looks for new efficient drugs like those used today, but less toxic. Knowledge of the molecular aspects of many of these compounds as well as the biochemical ways on which such compounds act, attract now more interest everywhere.